The Relationships between Types of Organizational Culture and Organizational Commitment: A Study on Hospitals at City Center of Elazig - Erdem, Ramazan (Eskisehir Osmangazi Univ, Fac Education, 2007)
The aim of this study is to determine types of organizational cuture of hospitals and to examine the relationships between types of organizational culture and organizational commitment. For this aim, it was reached 256 employees from six hospitals that have different characteristics in Elazig. Organizational culture questionnaire, developed by Deshpande et al. (1993) was used to determine types of organizational culture of hospitals; organizational commitment questionnaire, developed by Porter et al. (1974) and adabted to Turkish by Eriguc-Kaygin (1994) was used to examine levels of organizational commitment. It was found that hierarchy culture was high, and clan culture was low in hosptials. The relationships between types of organizational culture and organizational commitment were analyzed by stepwise regression model, and it was found that clan culture had a positive effect and market culture had a negative effect on organizational commitment.
Keywords: Types of organizational culture; organizational culture; organizational commitment